Philippine banking almanac - Litiatco, Vicki J. (Makati DRTI Consultancy (Phils), Inc., 1993)
A listing of Philippine banking institutions to aid businessmen and financial executives in the country. Includes selected articles by stalwarts in the banking community, primers on money market and trust operations. The almanac's highlight is its detailed listing of government and private banks in the country.
Contents: (part I) History of Philippine banking system. Monetary and fiscal policies. Government financial institutions. Industry outlook. (part II) List of banks, investment houses, offshore banking units, representative offices of foreign banks. Directories.
Purpose: An almanac on key banking institutions of the Philippines. The Philippine banking almanac is divided into two parts: Part I, which contains articles from personalities in the banking community, and Part II, which contains comprehensive information about Philippine banking institutions like basic data, financial highlights, board of directors, and domestic and international branches.
This almanac was published with realising the need of businessmen and business executives, particularly financial executives, for a comprehensive reference and guide on Philippine banking institutions. "Standard information which the reader may find are basic data (i.e. addresses, telephone with fax numbers), financial highlights (1989 to June or September of 1992), numbers of the board of directors and key officers, domestic and international branches (branch managers, addresses, telephone and fax numbers as of November 1992), products and services. It exists in two parts. Part I includes selected articles by stalkwarts in the banking community, including primers on money market and trust operations. Part II was collated from 1990-91 annual reports of banks, the Central Bank of the Philippines, SEC and fact sheets submitted by the bank. The almanac also included historical data (whenever possible, from the founding date), ownership structure, affiliates and subsidiaries, other business connections of the members of the board of directors, correspondent banks and other useful information (directories of Megalink, Banknet, Expressnet ATMs)." Also includes an index.
Jointly published by Ventures Unlimited in cooperation with the Businessman.
Keywords: Banks and banking -- Philippines -- Handbooks, manuals, etc; Banks and banking -- Philippines -- Directories; Banks and banking -- History. -- Philippines; Financial institutions -- Philippines